Clock Synchronization between Observational Units in the Arctic Tundra - Karlstad, Sigurd (UiT Norges arktiske universitet, 2021)
The arctic tundra is one of the ecosystems that is most affected by climate changes. The effects of these changes on the wildlife in the arctic are therefore critical to monitor. To monitor the changes, small computing devices with sensors and cameras, known as Observational Units, can be used. Using a cluster network of interconnected observational units, so that data can be reported from the most distant nodes to a homebase, introduces problems as the node’s local clocks tend to skew away from each other based on the environment they are in. This thesis aims to address the problem of clock synchronization in cluster networks that are disconnected from constant power and the internet. This thesis describes how we designed, built, and tested a prototype software solution for an interconnected Wireless Sensor Network using observational units built for arctic climates. We designed and built a two-phased system where the nodes dynamically join a network and synchronize their duty cycling and clocks with each other, creating a synchronized cluster of nodes that allows for data to be propagated, where any of the nodes can become sink nodes if they have a connection to a homebase. The nodes use a built-in clock synchronization operation to achieve synchronized clocks across the cluster network. The prototype system can perform the operations as planned. However, the results show that the system scales poorly when introducing new sinks to the network while running in the operational phase, as the paths shared scales exponentially, in contrast to when a sink is introduced in the starting phase of the system, where the transmissions grow linearly with a degree based on the number of nodes in the network. The time synchronization experiments also showed that the network is able to remain synchronized, although transmission number is a concern when the network does not have any sink nodes.